2021
DOI: 10.1002/kjm2.12376
|View full text |Cite
|
Sign up to set email alerts
|

4‐Phenylbutyric acid, a potent endoplasmic reticulum stress inhibitor, attenuates the severity of collagen‐induced arthritis in mice via inhibition of proliferation and inflammatory responses of synovial fibroblasts

Abstract: 4-Phenylbutyric acid (4-PBA) exerts potent pharmacological effects, including antiinflammatory properties, via inhibition of endoplasmic reticulum (ER) stress. However, it is not known whether 4-PBA attenuates the severity of rheumatoid arthritis. The present study aimed to determine whether the inhibition of ER stress by 4-PBA ameliorated experimentally induced arthritis. The proliferation of synovial fibroblasts (SFs) and expression of matrix metalloproteinases (MMPs) were evaluated in the presence of interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…A previous study demonstrated that 9-HODE is a pro-inflammatory mediator through the GPR132 receptor on monocytes and macrophages ( 46 ). In addition, 4-phenylbutyric acid is known to inhibit ER stress and reduce the levels of inflammatory mediators ( 47 ). Interestingly, some of the glycolytic enzymes have multiple functions in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that 9-HODE is a pro-inflammatory mediator through the GPR132 receptor on monocytes and macrophages ( 46 ). In addition, 4-phenylbutyric acid is known to inhibit ER stress and reduce the levels of inflammatory mediators ( 47 ). Interestingly, some of the glycolytic enzymes have multiple functions in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…1B), and 4-PBA (Figs. 1C and 1D) from previous studies and repeated experiments [21,23] . The signi cant reduction in cell viability in the Cd treated group demonstrates the important toxic effect of Cd on hepatocyte injury (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…4-Phenylbutyrate (4-PBA) can promote protein folding; it is a chaperone protein and considered an ERS inhibitor because it can promote the folding of unfolded proteins [19,20] . Studies have shown that ERS is the pathogenesis of many diseases, and 4-PBA exhibits the ability to alleviate ERS [21] . Research has demonstrated that as a chaperone of unfolded proteins, 4-PBA can rescue cells from apoptosis by reducing ERS [22] .…”
Section: Introductionmentioning
confidence: 99%